2014
DOI: 10.1007/s00464-014-3883-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrent or refractory strictures and outcome of endoscopic dilation for radiation-induced esophageal strictures

Abstract: Background Radiation therapy for head, neck, and esophageal cancer can result in esophageal strictures that may be difficult to manage. Radiation-induced esophageal strictures often require repeat dilation to obtain relief of dysphagia. This study aimed to determine the long-term clinical success and rates of recurrent and refractory stenosis in patients with radiation-induced strictures undergoing dilation. Methods Retrospective cohort study of patients with radiation-induced strictures who underwent endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 37 publications
1
27
2
Order By: Relevance
“…It supports previous data that also exposed an increasing number of dilations during the first year as a predictive factor for non-responsive PES [7] and severely narrowed strictures as a challenging situation [2,8]. Although other characteristics with recognized association to difficult treatment in this setting of aetiology, as stricture length, complexity, and location [8,9], would add value to this analysis if available in a larger population sample. Interestingly, refractory strictures did not present as a worse condition in this population and the authors suggested that these patients may still benefit from endoscopic therapy.…”
supporting
confidence: 86%
“…It supports previous data that also exposed an increasing number of dilations during the first year as a predictive factor for non-responsive PES [7] and severely narrowed strictures as a challenging situation [2,8]. Although other characteristics with recognized association to difficult treatment in this setting of aetiology, as stricture length, complexity, and location [8,9], would add value to this analysis if available in a larger population sample. Interestingly, refractory strictures did not present as a worse condition in this population and the authors suggested that these patients may still benefit from endoscopic therapy.…”
supporting
confidence: 86%
“…A recent meta-analysis [7] reported an estimated overall clinical success rate per patient (with a post-chemotherapy and RT or RT alone stricture) of 72.9% (95% CI 65.7-80.1%), with data suffering from significant heterogeneity as success was defined by resolution or improvement of different dysphagia scales. Previous findings stated that a soft/ normal diet may be achieved in > 70% [12,16,23,28] compared to 60% reported in our cohort. On the other hand, our dysphagia improvement perception rate was 58.3% Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…We designed our definition of overall efficacy as a trilogy where dysphagia improvement assessed as a "patient-reported outcome" needs to be associated with a 6-month period of absence of further dilations and PEG feeding. These criteria made our efficacy definition more demanding and therefore hard to compare with previously described endoscopic dilation efficacy rates [2,12,15,16,18,20,23]. A recent meta-analysis [7] reported an estimated overall clinical success rate per patient (with a post-chemotherapy and RT or RT alone stricture) of 72.9% (95% CI 65.7-80.1%), with data suffering from significant heterogeneity as success was defined by resolution or improvement of different dysphagia scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less satisfactory results in caustic strictures can be explained by a longlasting local inflammatory process that leads to a transmural process, tissue fibrosis, and irreversible deposition of collagen [22]. Caustic strictures, peptic strictures, and complex strictures were associated with a greater need for subsequent dilatations.…”
Section: Discussionmentioning
confidence: 99%